Effects of Acute Alcohol Intoxication on Testicular Dna Stability, Gene Expression of Cytochromes CYP3A and CYP2E1, and Serum Pool of Free Amino Acids in Rats - Larysa Bondarenko; Ganna Shayakhmetova; Olga Kharchenko; Maria Kalachinskaya; Natalia Serhiichuk; Valentyna Kovalenko; Olexandr Besarab (Innovative Biosystems and Bioengineering)
Background. Alcohol's toxic effects on the organism is a long-known medical problem. Alcohol's damaging effect is the end result of the complex interplay between ethanol metabolism, inflammation and innate immunity. Previously, we studied the long-term consequences of chronic alcoholism and demonstrated that especially profound changes were in testes on the level of proteome and genome.